STRATEGI KEPALA SEKOLAH DALAM MENGELOLA SARANA DAN PRASARANA UNTUK MENINGKATKAN MUTU PELAYANAN DI TK: STUDI KASUS TAMAN KANAK-KANAK BINAYOGA - Rullis Indriyanti; Siti Maisaroh (STKIP Subang, 2026)
ABSTRACT This study aims to describe and analyze the strategies implemented by the school principal in managing facilities and infrastructure, us well as their impact on improving the quality of educational services in kindergarten. This research employs a qualitative method with a descriptive approach. Data collection was carried out trough interviews, direct observation, and reviews of relevant document. The result show that the applied strategies include careful planning, procurement adjusted to the need and characteristics of early childhood, optimal arrangement and utilization, as well as continuous maintenance and care. In addition, the principal also encourages the active participation of educators, education staff, and parents in maintanining the completeness and suitability of facilities and infrastructure. Such well-directed and systematic management has proven effective in creating a safe, comfortable, and stimulating learning environment for children, which ultimately contributes significantly to improved service quality, parental satisfaction, and the overall quality of education delivery in the kindergarten. Thus study concludes that the principal’s competence in planning, organizing, utilizing, and maintaining facilities and infrastructure is a key determining factor in delivering quality educational services that align with national standarts for early childhood education.